Good Physician Adherence to Guideline-Directed Medical Therapy Associated with Lower Patient Mortality and Hospitalisation Rates Across The World - Mohammad Saifur Rohman (Heart Science Journal, 2020)
While the guidelines for the managements of heart diseases have been well-developed and updated periodically, they do not guarantee to reduce the number of heart disease morbidity and mortality. Since the holistic approach is not carefully applied, this morbidity rate may not be significantly reduced. The holistic approach to managing heart disease has broad aspects, but the most important aspect is regarding physician adherence to Guideline-Directed Medical Therapy (GDMT). This paper aimed to discuss the physician adherence to GDMT, and its role in reducing morbidity and in-hospitalization in heart disease patients. Several large scale studies have revealed that good adherence to heart failure treatment guidelines among physicians improved not only quality of life but also resulted in a better prognosis. On other hands, because the main target of physicians adherence to GDMT is to achieve maximally tolerated dose, it is also important that the understanding when and how to add, switch, and titrate all therapies to maximally tolerated doses and ideally target doses is important to reduce the morbidity and mortality of heart disease patients. However, in some points, this principle might not be applied properly due to several limitations. In this case, physicians may have to consider the balance between patients preferences, healthcare resources, and the risk of adverse outcomes. In conclusion, it should be noted that physician adherence to GDMT has an important role to reduce morbidity and mortality of heart disease patients.